127k views
3 votes
The first term of a geometric sequence is -2 and the common ratio is 3, What is the sixth term of the sequence?

Also, Write the Recursive Rule fo the seqeunce from above ^

1 Answer

5 votes

Answer:

a₆ = - 486

Explanation:

The nth term of a geometric sequence is


a_(n) = a₁
(r)^(n-1)

where a₁ is the first term and r the common ratio

Here a₁ = - 2 and r = 3 , then

a₆ = - 2
(3)^(5) = - 2 × 243 = - 486

The recursive rule allows a term in the sequence to be found by multiplying the previous term by the common ratio, that is


a_(n) = 3
a_(n-1) with a₁ = - 2

User Mark Schulz
by
6.2k points